MODEL PENDAYAGUNAAN PERPUSTAKAAN DESA UNTUK PENINGKATAN PENDIDIKAN MASYARAKAT DI DESA JIWOREJO, KECAMATAN JIKEN, KABUPATEN BLORA - Arif Sofianto (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2015)
Traditional Islamic Boarding School Miftakhul Amal in Jiworejo Village features a library, but it is not managed properly. This study aims to 1). Understanding the conditions that exist the library in the village Jiworejo, 2 ). Analyzing needs repairs that need to be done to optimize the function of the library in the village Jiworejo, 3). Analyzing the effort required to optimize the library in the village Jiworejo as a means for public education. This research is applied with a qualitative approach. The data analysis technique used in this study is an interactive model developed by Miles and Huberman. The conclusion of this study is; 1). Conditions the library in the village Jiworejo not function optimally because of the lack of cooperation, resource , collection , service , community acces , and reading culture . 2 ) . Efforts need to do is to establish cooperatio , explore the potential of the resourc , the addition of the collection, increasing of the service, open access to the public, as well as improving the reading culture of society. 3). Efforts to optimize the library as a means for public education by improving the capacity of the library, providing additional services aimed at attracting the public in the form of skills training, knowledge and entertainment.